Implementasi Pendidikan Agama Islam dalam Membentuk Karakter Siswa SMP Makarti Mandiri Sungai Nibung - Edi Purwanto; Irhamudin; M. Zainal Arifin (Attractive : Innovative Education Journal, 2024)
The purpose of this study was to determine the implementation of Islamic religious education in shaping the character of students at SMP Makarti Mandiri Sungai Nibung. This study is a qualitative study with the research subjects being the principal, Islamic Religious Education teachers and grade VIII students of SMP Makarti Mandiri Sungai Nibung. Data analysis in this study is data reduction, data presentation and drawing conclusions using an inductive thinking pattern. Education should not only transfer knowledge and science. Education must be able to make students have more knowledge and good morals. If education is limited to cognitive changes that result in not knowing to knowing, then what will happen in everyday life is that students are smart without being balanced with good morals. For this reason, character education should be instilled in education so that students are smart in knowledge and also smart in morals and ethics. So that students are able to practice character education in everyday life. Based on the results of the discussion above on how the implementation of Islamic Religious Education in forming character in students of Makarti Mandiri Sungai Nibung Middle School, it can be concluded that the methods of forming character in students of Makarti Mandiri Sungai Nibung Middle School include: Exemplary Method (al-Uswah al-Hasanah), Habituation Method (Ta'widiyyah), Mau'izhah and Advice Method, Qashash Method (Story), Amtsal Method (Parable) and Tsawab Method (Reward) and 'Iqab (Punishment).